Študij interakcije med vodikom in titanom z jedrsko spektroskopsko metodo ERDA - Zorko, Benjamin (Vakuumist, 2001)
For studying the system of hydrogen and titanium the ion beam analytical method ERDA (Elastic Recoil Detection Analysis) was used. The time evolution of hydrogen depth profiles in thick titanium samples were measured. The samples were etched in a solution of different acids and annealed in a vacuum chamber at 600 degrees C. Afterwards the samples were heated up to a certain temperature from 20 degrees C to 400 degrees C and exposed to the hydrogen molecules for 2000 seconds. The pressure in the vacuum chamber was changed from 10sup-6 mbar to 10 mbar. The escape of the hydrogen atoms from the samples was monitored at 380 supo C for several hours. From results of the measurements with ERDA method to diffusion coefficient of hydrogen cleaned titanuim in the order of 10 sup -12 cm supssup-1 was determined by suitable modelling. This value is many orders smaller than the value of the difussion coeficient of hydrogen in pure titanuim. The difference between the values show up that a thin layer of carbon and oxygen adsorbed on the surface of the sample slow down the mobility of hydrogen atoms in the sub-surface region. The amount of oxygen and carbon atoms in the sample were determined by menas of the NRA (Nuclear Reaction Analysis) method.
Keywords: titan; vodik; vezava; interakcije; jedrske spektroskopske metode; ERDA; ultravakuum